1987
DOI: 10.1017/s0140525x00055345
|View full text |Cite
|
Sign up to set email alerts
|

Précis of Relevance: Communication and Cognition

Abstract: In Relevance: Communication and Cognition, we outline a new approach to the study of human communication, one based on a general view of human cognition. Attention and thought processes, we argue, automatically turn toward information that seems relevant: that is, capable of yielding cognitive effects-the more, and the more economically, the greater the relevance. We analyse both the nature of cognitive effects and the inferential processes by which they are derived. Communication can be achieved by two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
711
0
82

Year Published

1992
1992
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 807 publications
(816 citation statements)
references
References 58 publications
5
711
0
82
Order By: Relevance
“…One hypothesis is that pragmatic interpretations, like scalar implicatures, generally occur by default unless otherwise cancelled by the context (Levinson, 2000). Others argue that all pragmatic interpretations, including implicatures, are constructed with reference to the global situation, rejecting notions of default inferences (Sperber & Wilson, 1986). While our study was not specifically designed to distinguish these two accounts, features of our data are compatible with predictions that each might make about language processing.…”
Section: Discussionsupporting
confidence: 64%
“…One hypothesis is that pragmatic interpretations, like scalar implicatures, generally occur by default unless otherwise cancelled by the context (Levinson, 2000). Others argue that all pragmatic interpretations, including implicatures, are constructed with reference to the global situation, rejecting notions of default inferences (Sperber & Wilson, 1986). While our study was not specifically designed to distinguish these two accounts, features of our data are compatible with predictions that each might make about language processing.…”
Section: Discussionsupporting
confidence: 64%
“…This has parallels with Sperber and Wilson's (1986) relevance theory of language use, in which utterances are tailored to be maximally relevant to the intended target, and also Gergely and Csibra's (2006) studies of pedagogical learning, in which human infants and adults have been found to exhibit species-specific cognitive adaptations to facilitate high-fidelity cultural transmission of behaviour when the efficacy or functional relevance of the behaviour is unclear. Chimpanzees have been found to have a contrasting tendency to preferentially acquire only those modelled actions that are functionally relevant to solving a task .…”
Section: R36 the Role Of "Intentionality"mentioning
confidence: 67%
“…These findings come from a set of studies designed to investigate children's sensitivity to a class of conversational inferences known as scalar implicatures (Carston, 1998;Gazdar, 1979;Grice, 1989;Harnish, 1976;Hirschberg, 1985;Horn, 1972;Levinson, 2000;Sperber & Wilson, 1995; among many others). Scalar implicatures arise in examples like Some students can write well where the speaker's use of some typically indicates that s/he had reasons not to use a more informative term, e.g.…”
Section: Discussionmentioning
confidence: 99%